Evaluating iodide recycling inhibition as a novel molecular initiating event for thyroid axis disruption in amphibians - Olker, Jennifer H. (Toxicol Sci, 2018)
The enzyme iodotyrosine deiodinase (dehalogenase, IYD) catalyzes iodide recycling and promotes iodide retention in thyroid follicular cells. Loss of function or chemical inhibition of IYD reduces available iodide for thyroid hormone synthesis, which leads to hormone insufficiency in tissues and subsequent negative developmental consequences. IYD activity is especially critical under conditions of lower dietary iodine and in low iodine environments. Our objective was to evaluate the toxicological relevance of IYD inhibition in a model amphibian (Xenopus laevis) used extensively for thyroid disruption research. First, we characterized IYD ontogeny through quantification of IYD mRNA expression. Under normal development, IYD was expressed in thyroid glands, kidneys, liver, and intestines, but minimally in the tail. Then, we evaluated how IYD inhibition affected developing larval X. laevis with an in vivo exposure to a known IYD inhibitor (3-nitro-L-tyrosine, MNT) under iodine-controlled conditions; MNT concentrations were 7.4-200 mg/L, with an additional ‘rescue’ treatment of 200 mg/L MNT supplemented with iodide. Chemical inhibition of IYD resulted in markedly delayed development, with larvae in the highest MNT concentrations arrested prior to metamorphic climax. This effect was linked to reduced glandular and circulating thyroid hormones, increased thyroidal sodium-iodide symporter gene expression, and follicular cell hypertrophy and hyperplasia. Iodide supplementation negated these effects, effectively rescuing exposed larvae. These results establish toxicological relevance of IYD inhibition in amphibians. Given the highly conserved nature of the IYD protein sequence and scarcity of environmental iodine, IYD should be further investigated as a target for thyroid axis disruption in freshwater organisms.